In Vitro Reconstitution of a Functional Duck Hepatitis B Virus Reverse Transcriptase: Posttranslational Activation by Hsp90 - Hu, Jianming (American Society for Microbiology, 2000)
Reverse transcription in hepatitis B viruses is initiated through a unique protein priming mechanism whereby the viral reverse transcriptase (RT) first assembles into a ribonucleoprotein (RNP) complex with its RNA template and then initiates DNA synthesis de novo using the RT itself as a protein primer. RNP formation and protein priming require the assistance of host cell factors, including the molecular chaperone heat shock protein 90 (Hsp90). To better understand the mechanism of RT activation by Hsp90, we have now mapped the minimal RT sequences of the duck hepatitis B virus that are required for chaperone binding, RNP formation, and protein priming. Furthermore, we have reconstituted in vitro both RNP formation and protein priming using purified RT proteins and host factors. Our results show that (i) Hsp90 recognizes two independent domains of the RT, both of which are necessary for RNP formation and protein priming; (ii) Hsp90 function is required not only to establish, but also to maintain, the RT in a state competent for RNA binding; and (iii) Hsp90 is not required during RT synthesis and can activate the RT posttranslationally. Based on these findings, we propose a model for Hsp90 function whereby the chaperone acts as an active interdomain bridge to bring the two RT domains into a poised but labile conformation competent for RNP formation. It is anticipated that the reconstitution system established here will facilitate the isolation of additional host factors required for RT functions and further elucidation of the mechanisms of RT activation.